Peran Kadar Hormon Estrogen pada Perempuan Obesitas Sebagai Faktor Terganggunya Siklus Menstruasi - Hasvia Berliani; Desmawati Desmawati; Bobby Indra Utama (Faculty of Medicine, Universitas Andalas, 2023)
Objectives: This study aims to determine the role of estrogen hormone levels in obese women as a factor in disrupting the menstrual cycle. Method: This Systematic Literature Review is based on articles from journals obtained through Pubmed, Science Direct and Google Scholar searches, referring to the topics that have been determined. The research articles used were selected with inclusion and exclusion criteria. Result: Obesity has a detrimental effect on the human body, including reproductive health. In particular, obese women are disturbed by the pituitary-ovarian-hypothalamic axis and often suffer from menstrual dysfunction leading to anovulation and infertility. Women with high levels of fat in their bodies will affect the hormone estrogen because apart from the ovaries, estrogen will also be produced by adipose tissue, making estrogen abnormal and tend to be high. This unbalanced hormone production can cause disturbances in the menstrual cycle. Conclusion: High estrogen levels cause the feedback to FSH to be disrupted so that it does not reach peak levels and interferes with follicle growth which causes the prolongation of the menstrual cycle (Oligomenrhea).